Embryo and Seed Germination of Pisang Klutuk Wulung (Musa balbisiana Colla) After Storage - Wulan Septiningtyas Kurniajati; Resa Sri Rahayu; Apriliana Dyah Prawestri; Ahmad Zaelani; Diyah Martanti; Herlina Herlina; Yuyu Suryasari Poerba (Biosaintifika: Journal of Biology & Biology Education, 2022)
Pisang Klutuk Wulung is one of Musa balbisiana accessions which has potential for genetic improvement of cultivated banana so that its conservation is essential. This research aimed to study the post-storage germination of Indonesian seeds of Pisang Klutuk Wulung. Storage methods were carried out using a factorial completely randomized design with three factors: packing methods using vacuum and non-vacuum plastic bags; storage temperature at 25ºC, 4ºC, and -20ºC; and storage duration by 7, 14, 30, and 50 days. The germinations were done in vitro and ex vitro. The results showed that seeds stored at 25ºC in non-vacuum plastic bags were infested by molds, contrasting to the non-vacuum treatment. The sterilization method using 25% sodium hypoclorite, Tween 20, and 80% alcohol resulted in less contamination than 96% alcohol. In vitro germination from the vacuum treatment had a higher germination rate than non-vacuum treatment. However, ex vitro germination was not affected by the storage method. Similar patterns were seen in vitro and ex vitro germination as storage in 4ºC resulted in better seed germination after 30 and 50 days. In contrast, at -20ºC, no embryo germinated in all storage duration treatments. Pisang Klutuk Wulung seeds could not be stored in the long term as they rapidly lost their viability. Our finding showed that airtight condition by vacuum treatment and low temperature at 4ºC were able to maintain seed viability for longer period of storage. Thus, this finding was useful to improve Musa breeding programs and as an essential step for the long-term conservation of Musa genetic resources.